2011
DOI: 10.1515/cclm.2011.697
|View full text |Cite
|
Sign up to set email alerts
|

New insights into adipose tissue dysfunction in insulin resistance

Abstract: In a state of caloric excess, adipose tissue plays an essential role by storing lipids. Its expandability determines the onset of metabolic syndrome (central obesity, dyslipidemia, glucose intolerance and hypertension). When the adipocyte endoplasmic reticulum is no longer capable of processing the excess nutrients, the so-called "endoplasmic reticulum stress" develops. This triggers efflux of free fatty acids from adipocytes into the circulation and causes triglyceride overload in skeletal muscle, liver and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 79 publications
2
52
0
4
Order By: Relevance
“…Levels of these markers were elevated in the wild-type mice on the HFD compared to those on the LFD, as expected (34)(35)(36)(37)(38), and, remarkably, were still more elevated in the NCoR Ϫ/Ϫ mice on the HFD despite the glucose tolerance of the latter (Fig. 5C, D, and F).…”
Section: Resultssupporting
confidence: 75%
“…Levels of these markers were elevated in the wild-type mice on the HFD compared to those on the LFD, as expected (34)(35)(36)(37)(38), and, remarkably, were still more elevated in the NCoR Ϫ/Ϫ mice on the HFD despite the glucose tolerance of the latter (Fig. 5C, D, and F).…”
Section: Resultssupporting
confidence: 75%
“…There is expansion of the adipose tissue depots in obesity with both hyperplasia and hypertrophy, coupled with increased macrophage infiltration and, consequently, inflammation. Although obesity can lead to an expansion of the visceral depot to as much as 20% total fat mass, subcutaneous adipose tissue accounts for the remaining 80% and also responds to inflammatory insults (Mlinar & Marc 2011). Furthermore, while adipose tissue from lean individuals may preferentially secrete anti-inflammatory adipokines such as adiponectin, transforming growth factor b (TGFb), interleukin 10 (IL10), IL4, IL13, ILRa and apelin, in obesity pro-inflammatory adipocytokines such as TNFa, IL6, leptin, visfatin, resistin, angiotensin II and plasminogen activator inhibitor 1 are released, as well as several interleukins (Ouchi et al 2011) coupled with a reduction in secretion of anti-inflammatory adipokines (Table 1).…”
Section: Adipose Tissue: a Site Of Inflammationmentioning
confidence: 99%
“…Results showed that overexpression of hDDAH-2 increased intracellular DDAH activity, decreased ADMA contents, and ameliorated insulin sensitivity by up-regulating IRS-1 and GLUT-4 expression. Since defect of insulin signal in adipocytes has been confirmed to be crucially important in metabolic diseases [27,28], we have reason to postulate that local DDAH-2 might be protective in maintaining insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%